The association between mental health and cognitive ability: Evidence from the Understanding Society survey - Syka Iqbal; Muhammad Waqas; Min Hooi Yong; Ronan McGarrigle; Eleftheria Vaportzis (PLoS ONE, 2025)
Background The relationship between poor mental health and cognitive impairments in older age is well-established. Social engagement also influences cognitive ability. However, current research has not simultaneously accounted for the interplay between mental health, social interaction, and socio-demographic factors. This study addressed this gap by using a large, nationally representative dataset to examine the associations between mental health, cognitive ability, social interaction, and key socio-demographic factors. Method In total, 7,685 individuals aged 65 or older were drawn from the UK Household Longitudinal Study Understanding Society. Cognitive abilities were assessed using self-reports and performance on five tasks (immediate and delayed word recall, subtraction, number series, and numerical ability). Mental health scores were derived from the General Health Questionnaire (GHQ-12). We controlled for social interaction, gender, ethnicity, educational background, marital status, number of children, and geographic location. Results We found positive relationships between mental health and all measures of cognitive ability except performance on subtraction, and number series tasks. These relationships remained after controlling for social interaction. Socio-demographic factors that contributed to the relationship between mental health and cognitive ability included being White and having higher education. Being male predicted better performance on numerical tasks, while being female, married or divorced predicted better performance on the verbal memory tasks. Conclusion We examined a wide range of cognitive domains using a large, nationally representative dataset. Overall, our findings provide novel insight into the relationship between mental health and cognitive abilities. This relationship persists when controlling for social interaction alongside socio-demographic factors in older adults, underscoring the importance of addressing these factors in policies and interventions for healthy ageing. Interventions should promote access to education, cognitive stimulation, and inclusive mental health services tailored to older adults.